2020
DOI: 10.1186/s42522-020-00025-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial drug resistant non-typhoidal Salmonella enterica in commercial poultry value chain in Chitwan, Nepal

Abstract: Background Antimicrobial resistance (AMR) among bacterial pathogens is a fast-growing public health concern. AMR in non-typhoidal Salmonella serovars (NTS) among food animals is of special concern as this may transmit resistant pathogens to humans during handling or consumption of animal products. In Nepal, the possibility of AMR Salmonella serovars among food animals is an important area of research, particularly in light of the rapidly growing poultry industry, lack of surveillance and proper biosecurity mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Salmonella isolated from poultry farms show critically high resistance to ampicillin (100%), amoxicillin (99%), and tetracycline (98%) in Bangladesh [44]. Salmonella isolated from poultry samples also show high resistance to colistin, ciprofloxacin, doxytetracycline, kanamycin, streptomycin, sulfamethoxazole, and tetracycline (42.1-97.6%) [5,6,[14][15][16][17]25]. The resistance patterns commonly observed in Salmonella isolates from poultry include amoxicillin-ampicillin-ciprofloxacin-erythromycin-gentamycin-penicillin-sulfamethaxole-tetracycline (26.4%) and ampicillin-streptomycin-amoxicillin/clavulanic acid-cephalothin-ceftiofur-cefoxitin (39.7%) [24,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella isolated from poultry farms show critically high resistance to ampicillin (100%), amoxicillin (99%), and tetracycline (98%) in Bangladesh [44]. Salmonella isolated from poultry samples also show high resistance to colistin, ciprofloxacin, doxytetracycline, kanamycin, streptomycin, sulfamethoxazole, and tetracycline (42.1-97.6%) [5,6,[14][15][16][17]25]. The resistance patterns commonly observed in Salmonella isolates from poultry include amoxicillin-ampicillin-ciprofloxacin-erythromycin-gentamycin-penicillin-sulfamethaxole-tetracycline (26.4%) and ampicillin-streptomycin-amoxicillin/clavulanic acid-cephalothin-ceftiofur-cefoxitin (39.7%) [24,44].…”
Section: Discussionmentioning
confidence: 99%
“…Poultry is known to harbor significant numbers of Salmonella serovars without showing clinical signs of the infection [3]. Salmonella prevalence is relatively high in chickens and, consequently, farm environments [4][5][6]. On the other hand, the infected flocks without previous vaccination could be result in almost 100% morbidity and about 20% mortality [7].…”
Section: Introductionmentioning
confidence: 99%
“…The rise of multidrug-resistant pathogens could be the result of improper maintenance of the use of antibiotics among food animals [14,22]. Studies from various countries have revealed the existence of antibiotic residues in poultry products [8][9][10][11].…”
Section: Prevalence Of Bacteria In the Poultry Productsmentioning
confidence: 99%
“…In Nepal, in spite of burgeoning poultry industry, proper biosecurity measures are often overlooked [6].…”
Section: Introductionmentioning
confidence: 99%